An RxLR effector from Plasmopara viticola suppresses plant immunity in grapevine by targeting and stabilizing VpBPA1. (19th August 2022) - Yin, Xiao; Fu, Qingqing; Shang, Boxing; Wang, Yunlei; Liu, Ruiqi; Chen, Tingting; Xiang, Gaoqing; Dou, Mengru; Liu, Guotian; Xu, Yan
SUMMARY: Grapevine downy mildew, caused by Plasmopara viticola, is one of the most devastating diseases in viticulture. Plasmopara viticola secretes RxLR effectors to modulate immune responses in grapevine. Here, we report an RxLR effector RxLR50253 from P. viticola that can interfere with plant immune response and thus promote pathogen colonization. RxLR50253 was induced at an early stage of P. viticola infection and could suppress elicitor (INF1 and Bax)‐triggered cell death. RxLR50253 promote pathogen colonization in both tobacco and grapevine leaves. VpBPA1 was found to be the host target of RxLR50253 by yeast two‐hybrid screening, and interaction between RxLR50253 and VpBPA1 was confirmed by multiple in vivo and in vitro assays. Further analysis revealed that VpBPA1 promoted pathogen colonization and decreased H2 O2 accumulation in transgenic tobacco and grapevine, while there was enhanced resistance and H2 O2 accumulation in NbBPA1 ‐silenced Nicotiana benthamiana leaves. Moreover, transient expression of VpBPA1 in NbBPA1 ‐silenced N. benthamiana leaves could reduce the accumulation of H2 O2 . Experiments in vivo demonstrated that RxLR50253 inhibits degradation of VpBPA1. Taken together, our findings showed that RxLR50253 targets and stabilizes VpBPA1 to attenuate plant immunity through decreasing H2 O2 accumulation during pathogen infection. Significance Statement: An RxLR effector RxLR50253 from Plasmopara viticola can interfere with plant immune response and thus promote pathogen colonization. VpBPA1 was found to be the host target of RxLR50253, and it can promote pathogen colonization in plants by decreasing the accumulation of H2 O2, and thus may play a negative role in plant disease resistance. RxLR50253 inhibits degradation of VpBPA1 to attenuate plant immunity through decreasing H2 O2 accumulation during pathogen infection.